Novel solution-processible small molecules based on benzo[1, 2-b:3, 4-b′:5, 6-b′′]trithiophene for effective organic photovoltaics with high open-circuit voltage. Issue 19 (30th January 2015) - Meng, Lucheng; Wu, Fen; Liu, Hailu; Zhao, Bin; Zhang, Jian; Zhong, Juan; Pei, Yong; Chen, Huajie; Tan, Songting
Abstract : Two novel A–D–A small moleculesD1 andD2, containing benzo[1, 2- b :3, 4- b ′:5, 6- b ′′]trithiophene as the central electron-donating unit and two thiophenes or three thiophenes as conjugated π-bridges, were designed and synthesized. Abstract : Two novel A–D–A small moleculesD1 andD2, containing benzo[1, 2- b :3, 4- b ′:5, 6- b ′′]trithiophene as the central electron-donating unit, 3-ethylrhodanine as end-capped electron-withdrawing units, and two thiophenes or three thiophenes as conjugated π-bridges, were designed and synthesized. The effects of the conjugated π-bridges on the photophysical, electrochemical and photovoltaic properties as well as the aggregation structure, were fully investigated. Compared withD2, D1 shows stronger packing capability, deeper HOMO energy levels, higher hole mobility, and more appropriate microphase separation with the fullerene derivative [6, 6]-phenyl-C61 -butyric acid methyl ester (PC61 BM), which lead to better photovoltaic performance with higher short-circuit current density ( J sc ) and open-circuit voltages ( V oc ). Bulk-heterojunction (BHJ) organic photovoltaic (OPV) devices were fabricated using a blend of the as-synthesized small molecules and PC61 BM in different solvents. TheD1-CF device prepared from chloroform solution with a weight ratio of 1 : 0.5 exhibited a power conversion efficiency (PCE) of 2.10% and an amazingly high V oc of 1.10 V under AM 1.5G (100 mW cm −2 ) illumination.